1992
DOI: 10.1111/j.1365-4362.1992.tb03980.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Predictive Factors in Late Recurrence of Stage I Melanoma

Abstract: Through the UCLA tumor registry, patients treated for late-relapse malignant melanoma (after a 10-year disease-free interval) were identified and studied retrospectively. The patients were studied in regards to age, sex, primary site of the lesion, the disease-free interval, elective lymph node dissection, mode of recurrence and survival time following relapse. The histologic characteristics studied included the maximal tumor thickness, Clark's levels, rate of mitoses, and presence of ulceration. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…28 Alternatively, if dormancy is a period of tumor stasis, with complete inhibition of net growth, and clinical recurrence results from an event that allows unrestrained proliferation, outcomes after recurrence of late and early patients should be equally poor. 14,13, 25, 29 Our data suggest each scenario is partially correct.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…28 Alternatively, if dormancy is a period of tumor stasis, with complete inhibition of net growth, and clinical recurrence results from an event that allows unrestrained proliferation, outcomes after recurrence of late and early patients should be equally poor. 14,13, 25, 29 Our data suggest each scenario is partially correct.…”
Section: Discussionmentioning
confidence: 70%
“…Most previous series of late recurrence lacked comparator populations and were unable to formally analyze risk factors. 1,12,14,17,18,21,23–26 Several suggested it was more common among pre-menopausal women, possibly with lower extremity primary lesions, while others disputed the suggestion. Other series used the overall melanoma population or those with no recurrence as comparators.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature on late local recurrences revealed only 18 cases that fit the criteria set above (Table 1) [1,[4][5][6][7][8][9][10][11]. However, unlike the current case, none of these patients experienced local recurrences in the same site more than once.…”
Section: Discussionmentioning
confidence: 91%
“…The Breslow thickness averaged 1.18 mm (range 0.4-1.85 mm). At follow up of varying lengths (range 5-216 months excluding the Otsu paper), five patients died of disease, four were alive with no evidence of disease, four were only reported as alive with no comment regarding disease status, three statuses were unknown, one experienced two local recurrences, and one had a regional and systemic disease in four years time but was still being treated at the time of reporting [3][4][5][6][7][8][9][10][11]. melanoma in the dermis with negative surgical margins.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Die Wahrscheinlichkeit einer spä-ten Progression nach 10 und mehr Jahren erscheinungsfreiem Intervall wird je nach Größe und Zusammensetzung des untersuchten Kollektivs und der Dauer der Nachbeobachtung mit 0,84-7% angegeben [4,7,15,19,24,36,42]. Aus der Reihe fällt der sehr hohe Anteil von 25% bei Crowley et al (1990).…”
Section: Malignant Melanoma · Late Metastasesunclassified